Chapter 12 Effekt av feedback på kollektiv mestringstro og sosial loffing i et sykkeleksperiment - Haugen, Tommy (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The aim of the study was to examine the extent in which verbal feedback (positive and negative) affected the collective efficacy, and to what extent an increase in collective efficacy would affect the propensity to social loafing in a sport group context where individual effort is not perceived as identifiable. 66 sports students conducted an interval of one-minute maximum effort on the bike ergometer under individual conditions. Participants were then randomized into teams in which half of them received positive feedback, while the others received negative feedback, before they then carried out three trials under collective conditions. The participants' belief in the team's victory chance was reported ahead of the second and third attempt. The results show that feedback affected the collective efficacy, but there was a non-significant difference in performance between the groups."